William Bratton and the NYPD : crime control through middle management reform - Nagy, Andrea R.; Podolny, Joel M. (Joel Marc) ([London] : SAGE, 2016)
William Bratton, commissioner of the New York Police Department from 1994 to 1996, presided over a dramatic decline in the city's crime rate. Hired by Mayor Rudolph Giuliani as part of a new crime fighting initiative, Bratton embraced the 'broken windows' theory that had made him so successful as chief of the city's transit police. This case examines the effectiveness of his approach.
Originally Published in: Nagy, A. R., & Podolny, J. (2008). William Bratton and the NYPD: Crime Control through Middle Management Reform. 07-015. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Bratton, William J; Organizational change -- Case studies; Middle managers -- Case studies; Police administration -- New York (State) -- New York -- Case studies